2013
DOI: 10.24297/ijmit.v7i1.715
|View full text |Cite
|
Sign up to set email alerts
|

A study on consumers perception for green products: An empirical study from India

Abstract: The last three decades have seen a progressive increase in worldwide environmental consciousness due to rising evidence of environmental problems. Environmental protection is increasingly becoming a necessity and part of a bigger agenda in the urbanising world of developing countries. Given the increasing deterioration of the environment, India as a developing country need to prevent pollution and preserve its natural resources. Environmental attitudes constitute a significant part of environmental consciousne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
(14 reference statements)
0
12
1
Order By: Relevance
“…A similar situation appears in the Indian context. While there are few studies estimating consumer WTP for environmentally sustainable food production (Mahapatra, 2013;Moser et al 2012), a considerable literature supports the view that Indian consumers are among the highest ranked according to environmental sustainability of their behaviour, preferring greener alternatives over non-green options (Ishaswini and Datta, 2011;Khan, 2012). This is consistent with expectations of green marketing growing in both practice and demand in India (Mishra and Sharma, 2010;Saxena and Khandelwal, 2010;Vernekar and Wadhwa, 2011;Shingrup, 2013;Mandal, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar situation appears in the Indian context. While there are few studies estimating consumer WTP for environmentally sustainable food production (Mahapatra, 2013;Moser et al 2012), a considerable literature supports the view that Indian consumers are among the highest ranked according to environmental sustainability of their behaviour, preferring greener alternatives over non-green options (Ishaswini and Datta, 2011;Khan, 2012). This is consistent with expectations of green marketing growing in both practice and demand in India (Mishra and Sharma, 2010;Saxena and Khandelwal, 2010;Vernekar and Wadhwa, 2011;Shingrup, 2013;Mandal, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of preferences for banana attributes Moser et al, (2012) found that consumers were WTP 27% more for bananas that had a low environmental impact, and 36% more for bananas that were pesticide free or 23% more if they were sprayed with bio-degradable pesticides. Mahapatra (2013) applied a non-specific generalised product framing when surveying consumers and found them WTP 5 to 10% more for goods that was produced using environmentally friendly production systems. Another M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…of the environment (Manaktola & Jauhari, 2007;Kilbourne & Pickett, 2008;Cheah & Phau, 2011). With regard to increasing environmental concerns, Indian consumers are on the same footing as global consumers (Jain & Kaur, 2004;Chitra, 2007;Mahapatra, 2013;Khan & Kirmani, 2014). According to Khan et al (2012), concern in India is mounting over an ever-growing list of environmental problems owing to increasing industrialisation as also pressure of growing population.…”
mentioning
confidence: 99%
“…Thus, CSR may be found to be strong contributor to consumer preference for a brand. The research (Mahapatra, 2013) brought out that among the most important factors influencing consumers’ preference and willingness to pay for herbal products are personal benefits, availability, fairness of price, ease of use and concern for environment and health. In a recent research (Misra & Singh, 2016), positive correlations were found towards the readiness to pay for eco-friendly herbal products and environmental consciousness, certification involvement and its perceived importance.…”
Section: Review Of Literaturementioning
confidence: 99%